Assessment of the Performance of Agricultural Tires Using a Mobile Test Bench - Roberto Fanigliulo; Marcello Biocca; Renato Grilli; Laura Fornaciari; Pietro Gallo; Stefano Benigni; Paolo Mattei; Daniele Pochi (Agriculture, 2022)
The performance of agricultural tires varies with the characteristics of both the terrain and the tractors on which they are mounted, which differently affect the rolling resistance, the traction capacity, and the slip. To reduce the variability of test conditions, CREA developed an original mobile test (MTB) bench which consists of a dynamometric single axle trailer pulled by a tractor and can be used both in traction performance tests (driving wheels) and in rolling resistance tests (driven wheels). A control system alternatively operates the adjustment of traction force or slip, so that each test is performed maintaining constant the desired values. The MTB underwent tests under different conditions (type of surface, pre-set values of force of traction and slip) aimed at verifying its accuracy and reliability. In a final test, two pairs of identical new tires were simultaneously mounted on the MTB and on the rear axle of the 2WD tractor that pulled it, to discover information on the different interactions occurring, under the same traction conditions, between the soil surface and each pair of tires, with reference to the relationship between the slips and the load transfers observed on the MTB and on the tractor rear axle. The results evidenced the capability of the MTB to guarantee repeatable test conditions, including field conditions, allowing comparison among the performance of different tires.